2019
DOI: 10.1101/850198
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A Zika Virus Primary Isolate Induces Neuroinflammation, Compromises the Blood-Brain Barrier, and Upregulates CXCL12 in Adult Macaques

Abstract: 22Zika virus (ZIKV) is a neurotropic virus that can cause neuropathy in adults and fetal 23 neurologic malformation following infection of pregnant women. We used a nonhuman primate 24 model, the Indian-origin Rhesus macaque (IRM), to gain insight into virus-associated hallmarks 25 42 chemokine may be involved in virus-induced inflammation and/or in repair of virus-induced brain 43 damage. Our data are significant since they help in understanding the mechanism of brain 44 damage caused by ZIKV in adults. 45 … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 53 publications
0
6
0
Order By: Relevance
“…The Zika virus (ZIKV) is a neurotropic virus that induces adult neuropathy. ZIKV infection causes an increase in CXCL12, which regulates lymphocyte trafficking through the BBB ( 220 ). After infecting brain microvascular cells, ZIKV is released on the parenchyma side, and it initiates the alteration of BBB integrity and upregulation of inflammatory and cell adhesion molecules ( 221 ).…”
Section: Infective Neuroinflammation and Neurodegenerationmentioning
confidence: 99%
“…The Zika virus (ZIKV) is a neurotropic virus that induces adult neuropathy. ZIKV infection causes an increase in CXCL12, which regulates lymphocyte trafficking through the BBB ( 220 ). After infecting brain microvascular cells, ZIKV is released on the parenchyma side, and it initiates the alteration of BBB integrity and upregulation of inflammatory and cell adhesion molecules ( 221 ).…”
Section: Infective Neuroinflammation and Neurodegenerationmentioning
confidence: 99%
“…However, these findings need further evaluation in vivo . Another study performed ZIKV infections in adult macaques revealed a high incidence of neuroinflammation in infected animals and a disruption of the BBB ( Figure 2 ) ( 147 ). Here, long-term increased levels of C-X-C motif chemokine ligand 12 (CXCL12), which is a chemokine involved in lymphocyte trafficking and neural repair, were described.…”
Section: Fetal Infectionsmentioning
confidence: 99%
“…Here, long-term increased levels of C-X-C motif chemokine ligand 12 (CXCL12), which is a chemokine involved in lymphocyte trafficking and neural repair, were described. Additionally, the authors observed inflammation in the perivascular space and meninges, accompanied by lymphocytic infiltrations ( 147 ). This was also reported in fetal human brains, where an infiltration of T and B cells was observed in the perivascular space during ZIKV infection ( Figure 2 ) ( 113 ).…”
Section: Fetal Infectionsmentioning
confidence: 99%
“…Gestational timing and type I interferon responses in utero are also critical in ZIKV susceptibility (16,17). Upon fetal infection, ZIKV also breaches the blood-brain barrier and infects susceptible neuronal tissue (18)(19)(20)(21)(22).…”
Section: Introductionmentioning
confidence: 99%
“…Gestational timing and type I interferon responses in utero are also critical in ZIKV susceptibility (17,18). Upon fetal infection, ZIKV also breaches the blood-brain barrier and infects susceptible neuronal tissue (19)(20)(21)(22)(23). Infection of these neuronal tissues is associated with direct tissue damage through the cytopathic effect (24)(25)(26), molecular level pathogenesis (27), disruption of cell division (24,(28)(29)(30), and dysregulation of developmental pathways (31)(32)(33)(34)(35)(36)(37).…”
Section: Introductionmentioning
confidence: 99%